The “fuero del Baylío”, with occasion of commentary of the judgment of the Appeal Court of Badajoz, 18th January 2019 - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The Appeal Court of Badajoz has returned to pronounce on the application of the Fuero del Baylío, on this occasion, in relation to a couple with civil vicinity in Valencia del Ventoso (Badajoz). The judgement afirms, once more time, the validity and applicability of this institution.
Keywords: Fuero del Baylío; matrimonial property regime; universal community property regime; community property regime; customary law; foral law; custom